CD44v, S1PR1, HER3, MET and cancer‐associated amino acid transporters are promising targets for the pancreatic cancers characterized using mAb - Takashi Nakano; Kouki Okita; Shogo Okazaki; Soshi Yoshimoto; Sachiko Masuko; Hideki Yagi; Kazunori Kato; Yoshihisa Tomioka; Kenichi Imai; Yoichi Hamada; Kazue Masuko; Kayoko Shimada‐Takaura; et al. (FEBS Open Bio)
Effective therapies have yet to be established for pancreatic ductal adenocarcinomas (PDAC) even though it is the most aggressive cancer. In the present study, PDAC was analyzed using novel rat mAbs against membrane proteins in conjunction with flow cytometry and immunohistochemistry. Human epidermal growth receptor (HER)1–4, mesenchymal to epithelial transition factor (MET), sphingosine‐1‐phospahate receptor 1 (S1PR1), l‐type amino acid transporter 1 (LAT1), system x−c transporter (xCT), alanine‐serine‐cysteine transporter (ASCT2), cationic amino acid transporter 1 (CAT1) and variant CD44 (CD44v) were expressed at high frequencies in both in vitro and in vivo PDAC. Internalization of membrane proteins by mAbs and growth inhibition by toxin‐linked mAbs were demonstrated in many PDAC cell lines, and mAbs against S1PR1, ASCT2, HER3 and CD44v inhibited the growth of xenografted MIA PaCa‐2 PDAC cells. Furthermore, CD44v‐high PDAC showed high mRNA expression of HER1–3, MET and CD44v, and was correlated with poor prognosis. Taken together, our results suggest that CD44v, S1PR1, HER3, MET and the above‐mentioned cancer‐associated amino acid transporters might be promising targets for the diagnosis and treatment of PDAC.